Negotiating Legal Pluralism: Managing Tensions between Islamic Law and Customary Law in Muslim Marriage Practices in Papua, Indonesia - Amri Amri; Lukman Ansar; Shofwan Al Jauhari; Mochammad Arifin; Ma'adul Yaqien Makkarateng (Justicia Islamica, 2026)
This research aims to describe the forms of conflict and negotiation that can arise between Islamic religious law and customary law in the practice of dowry (mahr) provision within Muslim Papuan marriages, to achieve a balanced coexistence. The primary focus of this study is to examine the forms of conflict and the conflict negotiation mechanisms that can be applied within the tradition of marriage dowry practices. This research employs a qualitative approach with a case study design focusing on Muslim communities of the Marind tribe in Merauke and the Dani tribe in Wamena, Papua, Indonesia. Data were collected through in-depth interviews, direct observation, and systematic documentation. After the research data were fully collected, they were processed and analysed using a descriptive contextual approach. The findings reveal that customary law is prioritised over religious law in determining marriage traditions. The continued existence and application of customary law have implications for tensions and conflicts with Islamic law. Therefore, marriage traditions, particularly the practice of dowry provision among Papuan Muslims, need to be reconstructed through negotiation in order to reconcile religious and customary law so that both may remain harmonious and coexist. Through restorative and normative–theological approaches, this study proposes a new model of negotiation that enables the continued practice of dowry provision based on customary rules without violating Islamic legal principles.